Herramienta web para el aprendizaje del manejo de técnicas de identificación odontológica forense - Mishell Pamela, Anrango Olmedo (2021)
ABSTRACT The present research project consisted of developing a web tool Dental Forense for learning forensic odontological identification techniques. The previous knowledge that the 58 students of the study population had at a conceptual and interpretative level of each of the identification cards (forensic, rugoscopic and cheiloscopic) was evaluated by means of the development of 3 different questionnaires. In the analysis of the results of the initial evaluation, it was found that the students had a high level of conceptual and interpretative ignorance of the 3 identification cards. The one with the highest percentage of ignorance was the cheiloscopic card. Through the statistical analysis with the chi-square statistical test, the relationship between the conceptual knowledge and the capacity of graphic interpretation that each of the 58 students of the study population possesses was evidenced, where the association of each one of the associations was accepted. The effective association between learning and the use of the Dental Forensic web system was also corroborated. Finally, it was concluded through the analysis of the results that there is an association between learning and the use of Dental Forensic, so it is recommended the use of Dental Forensic as a tool for learning the management of identification cards, promoting the development of new skills at the interpretative level. Key words: Forensic card, rugoscopic card, cheiloscopic card, identification techniques dentistry forensic Reviewed by: Lcda. Diana Chávez English Professor. c .c. 065003795-5